THE EFFECTS OF EARTHWORMS’ (PHERETIMA ASPERGILLUM) ETHANOL EXTRACT TOWARD THE IMPROVEMENT OF NERVE FIBERS DENSITY IN DIABETIC ULCERS CARE DEGREE II OF RATS WISTAR - Kristianto, Heri; Mardiati, Ni Putu Jeny (Malang Neurology Journal, 2017)
Background. Diabetic ulcer is a chronic complication of diabetes mellitus which lead to infection and lower extremity amputation. Earthworm (Pheretima aspergillum) has bioactive substance of IGF-1 (insulin like growth factor 1) to promote Schwann cell proliferation, survival, and migration into the distal end in the injured nerve area to support axonal re-growth.Objective. To investigate the effect of earthworm extract (Pheretima aspergillum) on the enhancement of nervous fibers density in rats induced diabetic ulcer stage II.Methods. This study applied a true-experimental posttest only controlled group design. Samples were divided into five groups: Normal Saline as a negative control group, Hydrogel as a positive control group, and the three treatment groups received earthworm extract via topical, oral, and topical-oral. The patterns of nervous fibers connecting to hair follicles were identified using silver impregnation stain.Results. The result shows the groups receiving earthworm extract have significantly higher nervous fibers density compared to the control groups (p=0.000). The administered of earthworm extract via topical has an optimal effect on improving nervous fibers density.Conclusion. Earthworm extract promote regeneration of peripheral nerve in rats model of diabetic.